(untitled) (Лучшие интеллектуальные исследования, 2025)
This article examines the importance of modern technologies in the development of innovations in the tourism sector. The share of innovative technologies in the tourism sector, the results in the sector and their current status are analyzed. Suggestions and conclusions are given on the effective use of innovations in the development of regional tourism.